Mechanisms linking trait emotional intelligence to contextual performance of teacher leaders: A PLS-SEM approach - Salisu, Bala; Awang, Siti Rahmah; Arsal, Muryani (Academic Journal of Psychology and Counseling, 2025)
There is a lack of understanding of how trait emotional intelligence (EI) impacts contextual performance and the mediating processes involved, especially in challenging contexts. Thus, the main purpose of this study was to address the under-researched relationship between trait EI and contextual performance, specifically exploring the sequential mediating roles of political skill and self-efficacy among teacher leaders in the challenging context of Northeast Nigeria. This study linked personality traits to teacher leader performance, mediated by EI, political skill, and self-efficacy, within the framework self-determination theory. Self-report data were collected from 292 teacher leaders (x̅ age = 45.08 6.87; x̅tenure = 15.50 7.21) in Nigerian polytechnics and analyzed using PLS-SEM in SmartPLS. The results showed a significant direct effect of trait EI on contextual performance, and a partial mediation of perceived self-efficacy in the relationship. Interestingly, while political skill correlates positively with both trait EI and contextual performance, it did not exhibit a significant mediating effect. However, the analysis revealed a significant overall sequential mediation effect involving both political skill and perceived self-efficacy, explaining 60.4% of the variance in contextual performance. Thus, the researchers recommend incorporating political skill and perceived self-efficacy in staff selection and assessment processes.